Urgency of Indonesia’s Emergency Regulation According To Perspective Emergency Constitusional Law In Face Pandemic - Masriyani, Masriyani; Nazifah, Nazifah; Badri, Muhammad; Siregar, Nella Octaviany (SASI, 2022)
Introduction: Legislation in Indonesia has provided a place for regulation in emergency situations, both at the constitutional and statutory levels. There are inconsistencies, both conceptually and practically in the use of the emergency clause in emergency regulations. Through this paper, the author would like to emphasize need for projection of revamping the laws and regulations related to emergency situation in Indonesia.Purposes of the Research: This study aims to analyze Indonesia’s emergency regulation according to perspective of emergency contitutional law of in the face of a Pandemic. Emergency situations they are Emergency State Law regime Article 12 of the 1945 Constitution, the use of Article 22 of the 1945 Constitution of the Republic of Indonesia, and the meaning of other emergencies in accordance with law.Methods of the Research: The research methodology used is normative juridical by approaching the laws and regulations (Statute Approach) and conceptual approach. From the approach to legislation, it aims to find out the rules related to emergency regulations. The legal materials were collected by means of a literature study, then the legal materials were analyzed in a qualitative juridical manner.Results of the Research: Results of his research, emergency option based on constitution which is represented by the phrase state of emergency in Article 12 of the 1945 Constitution gives great powers to emergency authorities, can deviate from democratic procedures in constitution and violate human rights, except for non-derogable rights. Activation of state of danger also results in lack of political and legal oversight.